Matthew Tyson Yates and the First Building of University of Shanghai - Na KONG (Journal of Research for Christianity in China (JRCC), 2024)
Dr. Matthew Tyson Yates was the first Baptist missionary to East China, laying a solid foundation for Baptist missions in East China. In honor of him, the Southern Baptist Convention once planned to establish “Yates College” in Shanghai, and the Shanghai Baptist University named its first large building “Yates Hall”. Based on the archives and historical materials, this study comprehends the missionary experience of Dr. Matthew Tyson Yates in China, summarizes the adjustments of the Baptist missionary policy in China in the “post-Yates era”, and analyzes the religious meaning behind the building of the Yates Hall, with a view to deepening the understanding and knowledge of Christianity in Shanghai since the late Qing Dynasty.